Characterization of the complete mitogenomes of Baillon's Crake Porzana pusilla and phylogenetic analysis - Lian, Ting (Mitochondrial DNA B Resour, 2021)
The complete mitochondrial genome of the Baillon's Crake Porzana pusilla (Gruiformes: Rallidae) are sequenced and annotated, which contained 37 typical genes. The length of the complete mitochondrial genome is 16,966 bp (GenBank No. MW043485), with As, Ts, Cs, Gs, and AT content of the mitochondrial genome is 32.1, 23.2, 30.9, 13.8, and 55.3%, respectively. All protein-coding genes started with ATN except COX1 and ND5, which start with GTG, and all protein-coding genes end with a complete triplet codon (TAA, AGG, AGA, and TAG), except COX3, which ends with an incomplete T. The ND3 gene of P. pusilla with an extra C nucleotide in 174 site. Phylogenetic analysis revealed that the new sequenced species of P. pusilla was closer to the clade of Porzana fusca and Porzana paykullii, and all three Porzana are clustered into one branch.